Analisis Yuridis Undang-Undang Nomor 18 Tahun 2008 Tentang Pengelolaan Sampah dengan Menutup Metode Open Dumping: Tinjauan Fiqh Siyasah - Dara Muhklishah Pulungan; Fauziah Lubis (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study analyzes the implementation of the prohibition on open dumping in Law Number 18 of 2008 concerning Waste Management and examines it from the perspective of Fiqh Siyasah. A total of 343 of 550 landfills still violate this prohibition, indicating a serious gap between law and practice. The main problem is the effectiveness of government policies in implementing the General Principles of Good Governance and the principle of public welfare. Using normative-juridical legal methods, the results show the failure of implementation to violate the General Principles of Good Governance, such as weak legal certainty and neglect of the principle of benefit. In Fiqh Siyasah, open dumping is a mafsadah (damage) that is contrary to Maqashid Syariah, reflecting the government's inability to realize the public welfare.